A novel phytochemical from Dipteris wallichii inhibits human β-secretase 1: Implications for the treatment of Alzheimer's disease. (October 2020) - Chetia, Pankaj; Mazumder, Muhammed Khairujjaman; Mahanta, Saurov; De, Biplab; Dutta Choudhury, Manabendra
Abstract: Alzheimer's disease (AD) is the most prevalent progressive neurodegenerative disease, and the most common cause of dementia. One of the histopathological hallmarks of AD is the accumulation of extracellular amyloid-β (Aβ) oligomers as neuritic plaques in brain. The Aβ oligomers are produced from amyloid precursor protein by the action of secretase enzymes, among which β-secretase 1 (BACE1) catalyses the rate-limiting step. Thus, BACE1 is one of the most important therapeutic targets in preventing deposition of the plaques, progression of the disease, and thus as a disease-modifying therapeutic strategy. The present study was undertaken to isolate and identify novel phytochemicals from the pteridophyte Dipteris wallichii, and to determine their pharmacological properties. A novel compound was eventually detected and named Dip-1, and its pharmacological properties were predicted using computational modelling. The compound was found to have pharmacophores similar to those of known BACE1 inhibitors. Thus, further studies were performed to determine its drug likeness, blood–brain barrier (BBB) permeability, inhibitory potential and IC50 value. The results were promising, and the compound was found to have high drug likeness and BBB permeability, and a potent inhibitor of BACE1, with IC50 value of 0.0372 nM. Thus, the present study reports a novel BACE1 inhibitor from the plant D. wallichii, and is significant owing to its therapeutic implication as a disease-modifying therapy for AD.